2021
DOI: 10.1007/s00253-021-11181-6
|View full text |Cite
|
Sign up to set email alerts
|

Infectious recombinant Senecavirus A expressing novel reporter proteins

Abstract: Senecavirus A (SVA) is an emerging picornavirus that has been associated with vesicular disease and neonatal mortality in swine. The construction of SVA virus carrying foreign reporter gene provides a powerful tool in virus research. However, it is often fraught with rescuing a recombinant picornavirus harboring a foreign gene or maintaining the stability of foreign gene in the virus genome. Here, we successfully generated recombinant SVA GD05/2017 viruses (V-GD05-clone) expressing the green fluorescent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Viruses containing reporter genes within their genomes are a useful tool for detection and/or quantification of viral replication and screening antiviral agents. In recent years, the SVA reverse genetic systems have been widely used to construct recombinant viruses to express foreign genes (Liu et al, 2020a(Liu et al, , 2021Wang et al, 2021). A high-throughput neutralization test and screening of antiviral drugs based on an EGFP reporter SVA virus have been established to measure Nabs and antiviral drugs 4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] method is used to detect BHK-21 cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses containing reporter genes within their genomes are a useful tool for detection and/or quantification of viral replication and screening antiviral agents. In recent years, the SVA reverse genetic systems have been widely used to construct recombinant viruses to express foreign genes (Liu et al, 2020a(Liu et al, , 2021Wang et al, 2021). A high-throughput neutralization test and screening of antiviral drugs based on an EGFP reporter SVA virus have been established to measure Nabs and antiviral drugs 4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] method is used to detect BHK-21 cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the foreign genes in these viral genomes became unstable after several passages. In order to circumvent this problem, Wang et al ( 100 ) inserted the green fluorescent protein (iLOV), red fluorescent protein (RFP) or nanoluciferase (Nluc) gene at the junction between SVA 2A and 2B and, in addition, a stop-restart translation element T2A was inserted into the side of the 2B product of SVA to retain the natural coding sequence of the viral protein surrounding the foreign gene. The author found that SVA with the iLOV tag can maintain a high level of stable passage in cells.…”
Section: Oncolytic Virus Encoding Reporter Genes For In Viv...mentioning
confidence: 99%
“…The polyprotein of senecavirus could be cleaved into twelve polypeptides, namely the L, VP1, VP2, VP3, VP4, 2A, 2B, 2C, 3A, 3B, 3C, and 3D. 28 Currently, senecavirus belongs to the family Picornaviridae, and there is only one species Senecavirus A in the Senecavirus genus. It is reported that senecavirus may cause vesicular disease in pigs.…”
Section: A New Putative Species In the Genus Senecavirusmentioning
confidence: 99%